2016
DOI: 10.1089/sur.2013.132
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Peri-Operative Oxygen and Incision Site Infection after Surgery for Perforated Peptic Ulcer: A Randomized, Double-Blind Monocentric Trial

Abstract: Supplemental 80% FiO2 during and for 6 h after open surgery for PPU, which reduces post-operative SSI, should be considered part of ongoing quality improvement activities related to surgical care, with few risks to the patient and little associated cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 44 publications
0
47
0
Order By: Relevance
“…66 The risk of SSI infection was significantly lower in the 80% group compared to the 30% group with 48%. 66 Another significant decrease of the incidence of SSI was reported in the study of Bickel et al 73 70 Evaluation of 400 patients showed no significant difference between groups. 70 In addition three comparable studies evaluated whether 80% supplemental inspired oxygen during and for one to two hours after cesarean delivery would decrease SSI.…”
Section: Supplemental Inspired Oxygenmentioning
confidence: 81%
See 4 more Smart Citations
“…66 The risk of SSI infection was significantly lower in the 80% group compared to the 30% group with 48%. 66 Another significant decrease of the incidence of SSI was reported in the study of Bickel et al 73 70 Evaluation of 400 patients showed no significant difference between groups. 70 In addition three comparable studies evaluated whether 80% supplemental inspired oxygen during and for one to two hours after cesarean delivery would decrease SSI.…”
Section: Supplemental Inspired Oxygenmentioning
confidence: 81%
“…78,80 Schietroma et al again investigated the effect of supplemental inspired oxygen but this time in a population of 239 patients who underwent open surgery for perforated peptic ulcer. 66 The risk of SSI infection was significantly lower in the 80% group compared to the 30% group with 48%. 66 Another significant decrease of the incidence of SSI was reported in the study of Bickel et al 73 70 Evaluation of 400 patients showed no significant difference between groups.…”
Section: Supplemental Inspired Oxygenmentioning
confidence: 81%
See 3 more Smart Citations